Projection of Target Drug Particle Size in Oral Formulations Using the Refined Developability Classification System (rDCS) - Kristian Beran; Eline Hermans; René Holm; Kia Sepassi; Jennifer Dressman (MDPI AG, 2023)
Dissolution limitations to oral absorption can occur if the time required for dissolution is longer than the transit time across the small intestine and/or if dissolution is slower than the drug's permeation through the gut wall. These limitations most often occur for poorly soluble drugs. A standard method for overcoming dissolution issues is to reduce the particle size of the (solid) drug. Building on the refined Developability Classification System (rDCS), this work establishes a novel set of equations with which the appropriate degree of particle size reduction needed to mitigate dissolution limitations to absorption can be calculated. According to the type of data available, the appropriate equation(s) for each situation can be applied. Three case examples are used to illustrate implementation of the equations: voriconazole, lemborexant and istradefylline. Although for voriconazole (rDCS Class I) target radius (rtarget) estimates indicate that particle size reduction is unnecessary, for lemborexant (rDCS Class I) a radius of ≤20 µm would be required to improve absorption. For istradefylline (rDCS Class IIb) the rtarget was approximately 12 µm. Results are commensurate with literature information for these three drugs, signaling that the equations are suitable for application to a wide variety of drug substances.